Hello,
This can be found here : Inclusion-exclusion principle - Wikipedia, the free encyclopedia
For a simple proof... :
P(at least one Ai)=
Now we know that
Apply this to and
Then try to go from here.
This is really confusing to me... how could I prove this?
If A1, A2, and A3 are three events and the union of A1 and A2 != 0 and the union of A1 and A3 !=0 but the union of A2 and A3 = 0 show that
P(at least one Ai) = P(A1) + P(A2) + P(A3) - 2P(A1 n A2)
Hello,
This can be found here : Inclusion-exclusion principle - Wikipedia, the free encyclopedia
For a simple proof... :
P(at least one Ai)=
Now we know that
Apply this to and
Then try to go from here.
Look at your question.
.
There very little there that makes any sense what so ever.
The notation is incorrect; the vocabulary is wrong.
Example: “union of A1 and A2 != 0” has no meaning whatsoever.
Neither does “the union of A2 and A3 = 0”.
We cannot possibly answer a posting that cannot be read.
You post is not readable.
I suspect that you don’t know union from intersection.
The inclusion/exclusion principle applied to probability function is: